The legal and practical aspects of trade with the Soviet Union. - Giffen, James Henry (New York, Praeger, 1969)
This legal documents provides a much of the controversy and myth-making surrounding U.S,-Soviet trade as a result of a lack of information and understanding.
Includes Appendixes
Includes bibliographies.
II 16/01/2019
Loans
Keywords: Soviet Union; United States